Memórias infocomunicativas: estudo das manifestações gastronômicas no seridó paraibano - Fernandes, Flora Constance Moura (2023)
Gastronomic information is an emerging topic in the area of Information Science, however, it has brought significant contributions to address the memory of food practices. In this sense, the research carried out is based on two infocommunicative modalities of the gastronomic experience of S eridó: the first, extracted from reports that make up the memory of the food experience, and for being a reference passed from generation to generation. The second comes from the records contained in recipe books, which are also ways to perpetuate gastronomic knowledge, a kind of memory that guides how to combine spices, herbs and foods to achieve culinary success. Through these infocommunicative records, we analyze how food practices socially configured the meal spaces in the Seridó region of Paraíba, at the height of cotton farming. The investigation strategy in based on the ethnographic approach, since the search for information that involves greater interaction for an adequate understanding and reading of the subjects. The understanding of gastronomic information, the subsequent culinary learning, food practice, and the consequent formation of culinary memory are perfectly collected in a methodological approach of documentary research associated with ethnographic research, that links what has already been recored and experienced to what memory has established as relevant and socially lived.